Integrating sporulation, toxin production and motility by redefining the role of TcdR and characterizing the sin region in Clostridium difficile - Parasumanna Girinathan, Brintha (Kansas State University, 2018)
Clostridium difficile is a gram-positive anaerobic, motile, spore-forming opportunistic bacterium. It is a nosocomial pathogen, and the symptoms of C. difficile infection (CDI) range from mild diarrhea to life-threatening pseudomembranous colitis and toxic megacolon. Antibiotic use is the primary risk factor for the development of CDI as it disrupts the healthy protective gut flora which enables C. difficile to colonize and establish in the colon. C. difficile damages the host tissue by secreting toxins and disseminates in the environment by forming spores. The two-major toxin-encoding genes, tcdA, and tcdB are located within a 19.6 kb pathogenicity locus (PaLoc), which also includes the gene encoding an RNA polymerase sigma factor TcdR, that is essential for toxin gene expression. We created a site-directed mutation in tcdR in the epidemic-type C. difficile R20291 strain and found that disruption of tcdR affected sporulation in addition to toxin production. Spores of the tcdR mutant were more heat- sensitive and required nearly three-fold higher taurocholate to germinate when compared to the wild-type (WT). Transmission Electron Microscopic analysis of the tcdR mutant spores also revealed a weakly assembled exosporium. Consistent with our phenotypic assays, our comparative transcriptome analysis also showed significant downregulation of sporulation genes in the tcdR mutant when compared to the WT strain. Our findings on tcdR suggest that the regulatory networks of toxin production and sporulation in C. difficile R20291 strain are interlinked with each other. Transcriptome analysis revealed the sin operon to be significantly downregulated in the tcdR mutant which made us hypothesize the link between sin operon regulation and sporulation. The sin locus coding SinR (113 aa) and SinI (57 aa) is responsible for sporulation inhibition in B. subtilis. SinR in B. subtilis mainly acts as a repressor of its target genes to control sporulation, biofilm formation, and autolysis. SinI is an inhibitor of SinR, and SinI/SinR interaction determines whether or not the SinR can inhibit target gene expression. The C. difficile genome carries two sinR homologs in the operon, and we named it as sinR and sinR’, coding for SinR (112 aa) and SinR’ (105 aa), respectively. To identify the regulation of sin on sporulation, we created a site-directed mutation in the sin locus in two different C. difficile strains R20291 and JIR8094. Comparative transcriptome analysis of the sinRR’ mutants revealed their pleiotropic roles in controlling several essential pathways including sporulation, toxin production, and motility (STM) in C. difficile. We performed several genetic and biochemical experiments, to prove that SinR regulates transcription of crucial regulators in STM pathways, which includes sigD, spo0A, and codY. Unlike B. subtilis, SinR’ acts as an antagonist of SinR and SinR’/SinR determines SinR activity. Our in vivo experiment using hamster model also demonstrated the importance of sin locus for successful C. difficile colonization. Our findings above reveal that sin locus acts as a central link that regulates essential pathways including sporulation, toxin production, and motility, which are critical for C. difficile pathogenesis. The final section of this dissertation analyzes a variant codY gene in the epidemic C. difficile R20291 strain. In this strain the CodY, a global nutrient sensor-regulator carry a missense mutation where the 146th tyrosine residue is replaced with asparagine (CodY[superscript Y146N]). Our preliminary study with the mutated CodY[superscript Y146N] suggested its differential role in its regulatory activity. Further analysis of CodY[superscript Y146N] might give some possible clues behind the hypervirulent nature of epidemic R20291 strain. Taken together, studies performed on both tcdR and sinR mutants reveal a significant amount of crosstalk occurring between the powerful regulators of STM pathways under the directionality of TcdR and SinR in determining their ultimate cell fate. Our findings on CodY[superscript Y146N] suggest how the bacteria could switch to a hypervirulence mode by manipulating one of its vital regulators like CodY.
Keywords: TcdR; SinR; Sporulation; Toxin; MotilityClostridium diffiicile